Beamline-implemented stretching devices for in situ X-ray scattering experiments. Issue 1 (1st December 2022) - Euchler, E; Sambale, A K; Schneider, K; Uhlig, K; Boldt, R; Stommel, M; Stribeck, A; Schwartzkopf, M; Rothkirch, A; Roth, S V
Abstract: Two recently developed experimental devices for investigating soft matter deformation are presented. Both devices exploit the capabilities of a modern synchrotron beamline to enable advanced and highly precise materials-science experiments in which X-ray scattering is registered. The devices can be operated both in monotonic as well as cyclic mode and are implemented into a beamline at DESY, Hamburg (Germany). Hence, relevant experimental parameters, such as displacement, force and temperature, are recorded synchronously with the individual X-ray scattering patterns. In addition, spatial variation of materials deformation can be monitored and recorded with optical microscopy. This unique sample environment enables in situ X-ray experiments in transmission, i.e. small- or wide-angle X-ray scattering (SAXS or WAXS), and in grazing-incidence geometry, i.e. grazing-incidence (GI-) SAXS or WAXS. One device with stepper motors is designed for studies of slow, (quasi-) static deformation and the other one with pneumatic actuators can be used for fast, impact deformation. Both devices are available to external beamline users, too.